An automated marking system for graphical user interfaces - Gray, Geoffrey Richard (2008)
This research investigates the feasibility and effectiveness of assessing students programming solutions to Graphical User Interface exercises in an automated fashion. Automated marking systems ease the burden on the staff involved in running a course and allow students to get results and feedback in a timely fashion. Several automated marking systems exist but are currently unable to mark GUIs. The inherent complexity of GUIs and the need for aesthetic analysis has rendered GUIs beyond the scope of most marking systems.